Chaplaincy : a comprehensive introduction - Jumper, Mark A., 1954- (Baker Academic, 2024)
"This comprehensive introduction covers the foundations of chaplaincy and surveys ten specific types of chaplaincy work, such as education, healthcare, the military, corporations, prisons, public safety, and sports"--
Includes bibliographical references and index.
Keywords: Chaplains